2012
DOI: 10.1254/jphs.12104fp
|View full text |Cite
|
Sign up to set email alerts
|

The T-type Ca2+ Channel Inhibitor Mibefradil Inhibits Voltage-Dependent K+ Channels in Rabbit Coronary Arterial Smooth Muscle Cells

Abstract: Abstract. We examined the effects of mibefradil, a T-type Ca 2+ channel inhibitor, on voltagedependent K + (Kv) channels in rabbit coronary arterial smooth muscle cells using the whole-cell patch clamp technique. Mibefradil reduced the Kv current amplitude in a dose-dependent manner, with an apparent K d value of 1.08 μM. Kv current inhibition by mibefradil was highly voltagedependent over the full activation voltage range (−30 to +10 mV). The decay rate of Kv channel inactivation was accelerated by mibefradil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
(30 reference statements)
0
10
1
Order By: Relevance
“…In contrast to mibefradil, NNC 55-0396 does not produce the metabolite responsible for inhibiting the L-type Ca 2+ channel (20) and was shown to improve tremor and myogenic tone (39,40). However, previous work and the present study have revealed that both mibefradil and NNC 55-0396 inhibit K V channels in arterial smooth muscle cells (19), suggesting that the structural similarities between mibefradil and NNC 55-0396 may contribute to K V -channel inhibition.…”
Section: +contrasting
confidence: 79%
“…In contrast to mibefradil, NNC 55-0396 does not produce the metabolite responsible for inhibiting the L-type Ca 2+ channel (20) and was shown to improve tremor and myogenic tone (39,40). However, previous work and the present study have revealed that both mibefradil and NNC 55-0396 inhibit K V channels in arterial smooth muscle cells (19), suggesting that the structural similarities between mibefradil and NNC 55-0396 may contribute to K V -channel inhibition.…”
Section: +contrasting
confidence: 79%
“…Mibefradil is also a LVA, T‐type Ca 2+ channel blocker (Mehrke et al, ; Martin et al, ), although its selectivity on LVA channels as compared to HVA channels is much smaller than that of NNC55‐0396, and effects on Ca v 1, Ca v 2,1, Ca v 2.2, and Ca v 2.3 channels have also been reported (e.g., Bezprozvanny and Tsien, ; Randall and Tsien, ; Jiménez et al, ). Moreover, mibefradil has been shown to also exert blocking effects on various types of Na + channels and K + channels (e.g., Liu et al, ; Eller et al, ; Hong et al, ; McNulty and Hanck, ). To avoid the consequences of such nonspecific actions on channels different from voltage‐gated Ca 2+ channels, we evaluated the effects of mibefradil not on original DAPs but on reconstructed DAPs generated by means of double‐ramp current stimuli in the presence of complete Na + ‐channel block with 1‐μM TTx (see above): it will be recalled, indeed, that the DAP reproduced in stellate cells under these conditions was still markedly Ca 2+ ‐dependent (see previous paragraph and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several research groups, including ours, have attempted to identify the side effects of chemicals that affect vascularKvchannelsbesidestheirownfunction.Forexample, curcumin (spice), the phosphoinositide-3 kinase inhibitor LY294002, the L-type Ca 2+ channels inhibitor verapamil, the T-type Ca 2+ channels inhibitor mibefradil, the protein kinase C inhibitor bisindolylmaleimide (I), and the guanylyl cyclase activator YC-1 directly inhibited vascular Kv channels in the open state. [26][27][28][29][30][31] In addition, the Ca 2+ channels inhibitor efonidipine and NNC 55-0396, as well as the tyrosine kinase inhibitor genistein and the protein kinase A inhibitor H-89 directly inhibited the vascular Kv channel in the closed state. 13,14,32,33) Furthermore, our group also reported that the protein kinase C inhibitor staurosporine and the calmodulin inhibitor trifluoperazine inhibited the vascular Kv channel in both open and closed states.…”
Section: Discussionmentioning
confidence: 99%